Mechanical and thermal properties of polylactic acid blended with recycled polymethyl methacrylate - Dehghani, Samaneh; Salehiyan, Reza; Pholharn, Dutchanee; Srithep, Yottha (Polymer engineering and science, 2025)
This study investigates the effect of incorporating recycled polymethyl methacrylate (r‐PMMA) into polylactic acid (PLA) and further modifications with a bio‐based compatibilizer (epoxidized soybean oil [ESO]). Various PLA:r‐PMMA ratios were evaluated, with and without ESO. Blending r‐PMMA into PLA significantly influenced mechanical properties. The 10PLA90r‐PMMA blend showed enhanced elongation at break (6.10%) and tensile toughness (1686 kJ/m3) compared to pure PLA (3.34% and 737 kJ/m3, respectively), addressing PLA's inherent brittleness. The 30PLA70r‐PMMA composition exhibited a tensile strength (TS) of 51.44 MPa and significant tensile toughness (1237 kJ/m3). Thermal analysis revealed an increase in the glass transition temperature (Tg) with higher r‐PMMA content, reaching 124°C for 100r‐PMMA, and a decrease in crystallinity percentage from 68.17% (pure PLA) to 30.43% (50PLA50r‐PMMA). Incorporating ESO into a 50 PLA50r‐PMMA blend modified its properties. Adding 3 parts per hundred resins (phr) ESO improved elongation at break (5.68%) and tensile toughness (1302 kJ/m3) while reducing TS (35.03 MPa). At 6 phr ESO, flexibility was maximized with an elongation of 6.37%, but TS decreased to 26.89 MPa. These findings highlight the synergy between r‐PMMA and ESO in enhancing PLA's performance for sustainable applications and balancing mechanical and thermal properties while addressing environmental challenges. Highlights r‐PMMA enhances PLA elongation (6.10%) & toughness (1686 kJ/m3) in blends. Pure PLA has 68.17% crystallinity; r‐PMMA lowers it to 30.43% in 50PLA50r‐PMMA. High r‐PMMA content erases melting peaks, indicating minimal PLA crystallinity. ESO boosts crystallization; 6 phr ESO in 50PLA50r‐PMMA increases it to 31.72%. r‐PMMA in PLA promotes sustainability via waste reuse & eco‐friendly materials. Effect of recycled PMMA and epoxidized soybean oil (ESO) on PLA blends. ESO enhances flexibility and toughness while balancing mechanical and thermal properties for sustainable applications.